Kinetics, kinematics, and muscle activity patterns during back squat with different contributions of elastic resistance - Shi, L.; Lyons, M.; Duncan, M.; Chen, S.; Han, D.; Yang, C. (International Journal of Sports Physiology and Performance, 2024)
Purpose Performing back squats with elastic bands has been widely used in resistance training. Although research demonstrated greater training effects obtained from adding elastic bands to the back squat, little is known regarding the optimal elastic resistance and how it affects neuromuscular performance. This study aimed to compare the force, velocity, power, and muscle activity during back squats with different contributions of elastic resistance.